Case Report: Hereditary spastic paraplegia associated with monoallelic variant in the motor domain of KIF1A - Sine, Kathryn; Brodie-Mends, David; Chouhani, Wafae; Massingham, Lauren; Alhusaini, Saud (Frontiers in Human Neuroscience, 2025)
ObjectivesTo investigate the genetic etiology of a familial case with spastic paraplegia.MethodsNeurological examination, clinical and genetic work-up, including exome sequencing (ES), followed by targeted testing, were performed to determine the underlying etiology of the patients’ phenotype.ResultsA 45-year-old man was initially diagnosed with spastic diplegic cerebral palsy in early childhood. He underwent multiple orthopedic interventions for lower extremities spasticity and progressive gait disturbance. His son developed similar neurological symptoms at 2-years of age. Despite unremarkable initial work-up, their relatively similar slowly progressive phenotype was suggestive of hereditary spastic paraplegia (HSP). ES was performed for the son at age 11 years, followed by cascade single testing for the father, which revealed a heterozygous (monoallelic) likely pathogenic variant [NM_001244008.2: c.947G > A (p.Arg316Gln); chr2-240775862] in exon 10 of the KIF1A gene.DiscussionKIF1A codes for a kinesin-3 motor protein involved in neuronal axon vesicular transport. KIF1A pathogenic variants are associated with several neurological phenotypes, most commonly HSP. The rare likely pathogenic variant (p.Arg316Gln) reported here was associated with an autosomal dominant HSP with few complications.